Ontogenetic, diurnal, and environmental impacts on VOC emission from sugarcane - Bin Hu; Ann-Mareike Jarosch; Rüdiger Grote; Mbezele Junior Yannick Ngaba; Jörg-Peter Schnitzler; Jürgen Kreuzwieser; Heinz Rennenberg (Environment International)
Sugarcane (Saccharum spp. hybrid) is a key crop for bioenergy production due to its high productivity in tropical and subtropical climates. Despite this economic importance, there is currently no information available on the emission of volatile organic compounds (VOCs) during the growth phase of this crop. This is despite the fact that the sustainability of sugarcane cultivation has been questioned due to the associated land-use changes and possible atmospheric pollution by VOCs. The present study investigated the VOC emissions from sugarcane and their dependence on ontogenetic, diurnal, seasonal and environmental factors. By GC–MS and PTR-MS analysis, the emission of 40 different VOCs from sugarcane leaves was recorded based on their molecular weight that were divided into seven chemical groups (i.e., alkanes, alkenes, aromatics, aldehydes, alcohols, ketones and terpenoids). In addition, complementary PTR-MS analysis showed strong emission of methanol, acetaldehyde and ethanol and minor release of monoterpenes, fatty acid derivatives (i.e., LOX products) and a compound with m/z 69 (which was not validated as isoprene). Compared to other bioenergy crops, e.g., maize, Salix, Miscanthus and poplar/aspen, terpenoid emissions play a quantitatively smaller role, indicating that sugarcane is a low impact species in terms of air chemistry. The VOC emissions from sugarcane leaves vary with plant developmental stages, during the day and between the seasons and are dependent on light intensity and temperature. Thus, our results could provide a valuable basis for future modelling efforts to upscale VOC emissions from sugarcane cultivation in different climatic zones.